“I definitely cannot afford to be feeling poorly if there’s no need to be”: a qualitative evaluation of antiviral uptake following suspected occupational exposure to avian influenza - Riinu Pae; Lucy Findlater; Richard Amlôt; Fernando Capelastegui; Gavin Dabrera; Clare Humphreys; Jharna Kumbang; Isabel Oliver (BMC Public Health)
Abstract Background Growing numbers of people have been potentially exposed to avian influenza (AI), as the United Kingdom has managed the largest and most sustained series outbreaks in recent years. Antiviral medication is recommended for exposed individuals for chemoprophylaxis to reduce the severity of illness and the likelihood of secondary transmission. However, some individuals have been hesitant or declined antivirals. In this study, we aimed to identify the factors affecting the uptake of and adherence to antiviral medication. Methods We interviewed 14 individuals occupationally exposed to avian influenza and conducted focus groups with 15 public health professionals involved in advising and arranging antivirals. The data were analysed thematically based on COM-B factors (capability, opportunity, motivation). Results Although participants saw avian influenza as a severe disease, most did not consider themselves susceptible to it because they felt safe in personal protective equipment and knew that bird-to-human transmission was rare. The biggest barrier to uptake and adherence was experiencing side effects, especially if these disrupted day-to-day life or work. Participants who took antivirals followed medical advice in a novel situation, had health conditions or vulnerable family members they wanted to protect. As responding to an outbreak was exhausting, easy access to antivirals for those at most risk was considered important for improving uptake. Conclusions The factors affecting antiviral uptake were multifaceted. Public health interventions should prioritise those at most risk and address multiple components of behaviour, such as advising how to manage side effects, addressing concerns about long-term usage and providing convenient access to antivirals for those at most risk.